2004
DOI: 10.1103/physreve.69.046115
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase phenomena, minority games, and herding models

Abstract: The recently discovered two-phase phenomenon in financial markets [Nature 421, 130 (2003)] is examined with the German financial index DAX, minority games, and dynamic herding models. It is observed that the two-phase phenomenon is an important characteristic of financial dynamics, independent of volatility clustering. An interacting herding model correctly produces the two-phase phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The second major result of this study is the synergetic effect of a model approach and a real data analysis. By attaching the nonlinear correlation structure of real financial data to the simulated returns from the model, herein the EZ model [7], and its modified version, slow convergence to a Gaussian behavior is explicitly observed in terms of scaling of moments. This additional algorithm of nonlinear correlations can be useful for generating many simulated returns, which are closer to the stylized features of real financial databases.…”
Section: Resultsmentioning
confidence: 99%
“…The second major result of this study is the synergetic effect of a model approach and a real data analysis. By attaching the nonlinear correlation structure of real financial data to the simulated returns from the model, herein the EZ model [7], and its modified version, slow convergence to a Gaussian behavior is explicitly observed in terms of scaling of moments. This additional algorithm of nonlinear correlations can be useful for generating many simulated returns, which are closer to the stylized features of real financial databases.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the two-phase phenomenon was again examined in the DAX financial index in [60] , using minority games and dynamic herding models. They found that this phenomenon is a significant characteristic of financial dynamics, independent of volatility clustering.…”
Section: Introductionmentioning
confidence: 99%
“…Li [70] for instance offered an agent modelling based explanation for some financial characteristics of assets returns while Zheng et al [71] rather focused on the agent-based modelling of herding behaviour combined with phase-transition analysis to describe financial dynamics. Wang [72] developed an evolutionary game theoretical model to describe the dynamics of wealth distributions in China.…”
Section: Econophysics Inmentioning
confidence: 99%